El rendimiento académico en el nivel de educación media como factor asociado al rendimiento académico en la universidad (2008)
This study intends to find the relationship between academic performance in High School and College, focusing on Natural Sciences and Mathematics. It is a descriptive correlational study, and the variables were academic performance in High School, performance indicators and educational history. The correlations between variables were established with Spearman’s correlation coefficient. Results suggest that there is a positive relationship between academic performance in High School andEducational History, and a very weak relationship between performancein Science and Mathematics in High School and performance in College.